CHAOS THEORY, GLOBAL SYSTEMIC CHANGE, AND HYBRID WARS - A. Korybko; H. Haddad (Сравнительная политика, 2016)
The global system is being rocked by the dueling ambitions of two competing blocs, with the US and its allies fighting to reinforce their unipolar system while Russia and its partners struggle to forge a multipolar future. The rapidity and scope with which events are unfolding makes it overwhelming for the casual observer to make sense of all of the complex processes currently at play, and truth be told, it’s understandable that all of this can appear confusing. In an attempt to clarify the present state of global affairs and forecast the direction that it’s all headed in, the article begins by explaining the nature of chaos theory and describing how it’s applicable to conceptualizing contemporary international relations. Afterwards, the idea of “chaos sequencing” is proposed, which in essence is a model that can be used in understanding the process of chaotic change. Following that, the article addresses the topic of global systemic change and includes the most relevant examples for how this relates to the present day. Next, the research combines these two aforementioned elements (chaos theory and global systemic change) and presents a forward-looking geopolitical analysis that incorporates cutting-edge Hybrid War theory and aims to put the New Cold War into its proper perspective. Finally, the article ends on a suggestive note in encouraging analysts to study the authors’ conceptualization of Hybrid War in order to better prepare themselves for understanding and responding to forthcoming international events.